2021
DOI: 10.1016/j.bbih.2021.100326
|View full text |Cite
|
Sign up to set email alerts
|

Three's Company: Neuroimmune activation, sex, and memory at the tripartite synapse

Abstract: The neuroimmune system is required for normal cognitive functions such as learning and memory in addition to its critical role in detecting and responding to invading pathogens and injury. Understanding the functional convergence of neurons, astrocytes, and microglia at the synapse, particularly in the hippocampus, is key to understanding the nuances of such diverse roles. In the healthy brain, communication between all three cells is important for regulating neuronal activation and synaptic plasticity mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 113 publications
(119 reference statements)
0
2
1
Order By: Relevance
“…No significant effects of Ptn overexpression or RPTPβ/ζ pharmacological inhibition were detected on gene expression of microglial markers Iba1 and Cd68 (a summary of PTN and MY10 effects on gene expression is presented in Table 3). It is important to note that other authors have reported sex differences in microglial states in healthy brains and in pathological conditions, such as stress or neurodegeneration [52][53][54]. However, in our experimental conditions, ethanol effects on prefrontal Iba1 mRNA levels are independent of sex.…”
Section: Discussioncontrasting
confidence: 50%
“…No significant effects of Ptn overexpression or RPTPβ/ζ pharmacological inhibition were detected on gene expression of microglial markers Iba1 and Cd68 (a summary of PTN and MY10 effects on gene expression is presented in Table 3). It is important to note that other authors have reported sex differences in microglial states in healthy brains and in pathological conditions, such as stress or neurodegeneration [52][53][54]. However, in our experimental conditions, ethanol effects on prefrontal Iba1 mRNA levels are independent of sex.…”
Section: Discussioncontrasting
confidence: 50%
“…In our studies, PFC and hippocampi of female mice showed enhanced morphological parameters of Iba1+ cells, compatible with a more activated state of microglia, independently of the treatment received. Sex differences in microglial state are known in the healthy brain and in conditions such as stress or neurodegeneration (Bilbo et al, 2012;Bollinger, 2021;Posillico, 2021) and are more evident in areas like PFC (Bollinger, 2021), where female rats show microglia with broadened morphology compatible with a surveillant phenotype. In this brain area, we found that these sex differences are more pronounced in animals treated with MY10 and ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences in basic and clinical PNI research are of increasing interest. In this special issue, Posillico (2021) provides a brief overview on synaptic plasticity for learning and memory involving neurons and astrocytes, a process also assisted by microglia. Sex differences in synaptic plasticity range from estrogen receptor distributions, transcription during hippocampal-dependent memory formation, intracellular signaling cascades, hippocampal neurogenesis, to differences in mechanisms and mediators of neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%